One-Pot Green Synthesis of Ag-Decorated SnO2 Microsphere: an Efficient and Reusable Catalyst for Reduction of 4-Nitrophenol - Hu, Min; Zhang, Zhenwei; Luo, Chenkun; Qiao, Xiuqing (Nanoscale research letters, 2017)
In this paper, hierarchical Ag-decorated SnO 2 microspheres were synthesized by a facile one-pot hydrothermal method. The resulting composites were characterized by XRD, SEM, TEM, XPS, BET, and FTIR analysis. The catalytic performances of the samples were evaluated with the reduction of 4-nitrophenol to 4-aminophenol by potassium borohydride (KBH 4 ) as a model reaction. Time-dependent experiments indicated that the hierarchical microspheres assembled from SnO 2 and Ag nanoparticles can be formed when the react time is less than 10 h. With the increase of hydrothermal time, SnO 2 nanoparticles will self-assemble into SnO 2 nanosheets and Ag nanoparticles decorated SnO 2 nanosheets were obtained. When evaluated as catalyst, the obtained Ag-decorated SnO 2 microsphere prepared for 36 h exhibited excellent catalytic performance with normalized rate constant ( κ nor ) of 6.20 min −1 g −1 L, which is much better than that of some previous reported catalysts. Moreover, this Ag-decorated SnO 2 microsphere demonstrates good reusability after the first five cycles. In addition, we speculate the formation mechanism of the hierarchical Ag-decorated SnO 2 microsphere and discussed the possible origin of the excellent catalytic activity.